Analisis Pengukuran Kinerja Pada PT XYZ Dengan Metode Balanced Scorecard dan Analytical Hierarchy Process (AHP) - Situmeang, Fabri Tobal H.; Akbar, Muhammad Deni; Santosa, Budi (Jurnal Ilmiah Wahana Pendidikan, 2024)
PT XYZ is a consulting, training, and certification services company. Historically, the company has measured its performance using traditional methods, focusing solely on financial aspects. This has resulted in poor company performance, evident through declining revenue due to decreased customer retention rates and operational inefficiencies. PT XYZ has also frequently received complaints from training participants regarding the company's operational processes. The most common complaint is the delayed issuance of certificates to participants. Furthermore, the employees at PT XYZ have a low level of technological proficiency because the company has not provided them with technology training. Based on these issues, there is a need for a comprehensive performance measurement method that can provide an in-depth assessment of the company's performance, allowing PT XYZ's management to make informed decisions to improve performance. Through the research conducted, it was found that the total performance scores, from a financial perspective, are 15.28; from a customer perspective, 23.19; from an internal business process perspective, 18.34; and from a growth and learning perspective, 15.15. Therefore, the overall company performance score is 71.10, indicating that it falls within the criteria of being reasonably healthy. Keywords — Analytical Hierarchy Process, Balanced Scorecard, Performance Measurement